Le touriste et le voyageur dans A Residence on the Shores of the Baltic (1841) d’Elizabeth Rigby - Stéphanie GOURDON (E-REA)
Although Elizabeth Rigby herself decided she would visit her sisters in Estonia, she was puzzled by the number of travellers from Western Europe exploring these areas. She perceived, more or less clearly, the dangers of a mass phenomenon which might distort an activity which had until then enriched human beings in many respects. This observation, as well as her fears and contradictions, led her to attempt a redefinition of travelling; yet, practical experience does not always confirm the constructs of the mind. This article highlights the way Rigby defines travelling and then considers what her travelling experience reveals. Unlike some of her fellow-writers, Elizabeth Rigby finds a middle way which does not totally reject the new form of travelling but which does not exclude her requirements either. And although she distinguishes between the ʽtouristʼ and the ʽcommitted travellerʼ one could almost call her a “committed tourist”.